2020
DOI: 10.1111/and.13709
|View full text |Cite
|
Sign up to set email alerts
|

Nano‐purification of raw semen minimises oxidative stress with improvement in post‐thaw quality of buffalo spermatozoa

Abstract: The dead and damaged spermatozoa present in the fresh ejaculates are carried passively along with the live ones into the processed semen. Such dead and damaged spermatozoa are primarily responsible for the production of reactive oxygen species (ROS). The detrimental effect by way of oxidative stress on the contemporary live spermatozoa results in poor fertility (Roca, Martinez-Alborcia, Gil, Parrilla, & Martinez, 2013). Since the buffalo spermatozoa show high lipid peroxidation (LPO) rate (Nair, Brar, Ahuja, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…It was observed that in the pellet left in test tube post nanopurification, there were clumps of dead and damaged spermatozoa bound with NPs. This observation draws supports from the findings of other investigations on the nanopurification of semen in different species [19,21,[46][47][48].…”
Section: Functionality Of Ionps-abs Complexsupporting
confidence: 90%
“…It was observed that in the pellet left in test tube post nanopurification, there were clumps of dead and damaged spermatozoa bound with NPs. This observation draws supports from the findings of other investigations on the nanopurification of semen in different species [19,21,[46][47][48].…”
Section: Functionality Of Ionps-abs Complexsupporting
confidence: 90%
“…The magnetic NPs did not impair the spermatozoa motility and their ability to fertilise oocytes (Ben-David Makhluf et al, 2006). The IONPs combined with 2.0 μg/ml anti-ubiquitin antibodies can be an efficient dose to decimate dead and impaired spermatozoa, reduce oxidative stress and increase the quality of post-thaw buffalo spermatozoa (Bisla et al, 2020). Understanding reactive oxidants and antioxidant | 9 of 16 status in extended semen and analysing their concentrations help in the in vitro manipulation of semen for ART (Aliakbari et al, 2016;Najafi, Adutwum, et al, 2018).…”
Section: Anti Oxidant S Tatus and Counter Ac Ting Oxidative S Tre Ssmentioning
confidence: 99%
“…NPs are conjugated with different ligands via ionic, hydrophobic, dative binding which is called as bio‐conjugation and it forms a basis of their many bio‐medical applications. Bio‐conjugation of NPs with antibodies (Abs), surface biomarkers & drugs is used in cancer diagnosis, drug delivery and other diagnostic & therapeutic applications (Bisla, Rautela, et al, 2020). NPs have different applications in the field of medical and veterinary sciences.…”
Section: Introductionmentioning
confidence: 99%
“…NPs have different applications in the field of medical and veterinary sciences. The emerging trends of using the NPs in the semen biology for various applications like depletion of dead/moribund and spermatozoa with various surface damages/alterations from the ejaculates (Nano‐purification of semen) (Odhiambo et al, 2014; Feugang et al, 2015; Durfey, Swistek, et al, 2017; Bisla, Rautela, et al, 2020; Bisla, Rautela, et al, 2021), bio‐imaging of gametes (Barchanski et al, 2015; Vasquez et al, 2016), sex‐sorting of semen (Domínguez et al, 2018; Moradi et al, 2021) and evaluation of male infertility using different biomarkers (Vidya & Saji, 2018) have opened the tremendous opportunities in the reproductive biology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation